PENGARUH AUDIT TENURE, ROTASI AUDIT DAN SPESIALISASI AUDITOR TERHADAP KUALITAS AUDIT - Tricia Rose Diana; Sofie Sofie (STMIK Widuri Jakarta, 2024)
This study aims to determine the effect of audit tenure, audit rotation and auditor specialization on audit quality in food and beverage manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the period 2020 to 2023. The type of data used is secondary data, namely data from financial reports. The data pooling method used in this study obtained 26 company samples. The data analysis model used is multiple regression analysis. The analysis tool used is SPSS. The results of the study show that audit tenure does not affect audit quality, audit rotation affects audit quality and auditor specialization does not affect audit quality.